School Year Plans. Bibliographies in Education No. 67 - Dohan, Margaret, Comp.; Canadian Teachers' Federation, Ottawa (Ontario). ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This bibliography lists 412 sources on school year plans published since 1970. Materials listed are broken down into books, articles, and theses, and their availability through the ERIC system is indicated. No annotations are provided. (PGD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Elementary Secondary Education; Foreign Countries; Scheduling; School Schedules; Year Round Schools; Canada; Reference Materials, Bibliographies